Peran Transformasi Digital dalam Peningkatan Nilai Ekonomi Produk PKBM Rizki Amalia, Desa Buntu Sarong, Kecamatan Masalle - Nurul Rahmawaty; Baharuddin; Saddam Ramli; Yunus Busa; Haerusman (Mataram University, 2026)
Digital transformation is a crucial need in the economic development of rural communities because it can expand market access, increase product competitiveness, and encourage business innovation based on local potential. However, the use of digital technology by coffee entrepreneurs in Buntu Sarong Village, Masalle District, is still not optimal, so the role of community empowerment institutions is needed to support the digitalization process. This study aims to describe the application of digital transformation in increasing the economic value of local coffee products, analyze the role of PKBM Rizki Amalia in supporting the process, and identify supporting and inhibiting factors that influence its success. This research is expected to provide benefits for the development of studies on non-formal education, community empowerment, and the digital economy based on local potential. The study uses a qualitative descriptive approach with a case study design conducted at PKBM Rizki Amalia Buntu Sarong Village, Masalle District, Enrekang Regency in 2026. The main research instrument is the researcher with supporting instruments in the form of interview guidelines, observation, and documentation. Data sources consist of primary and secondary data collected through observation, in-depth interviews, and documentation. Data analysis used the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. Data validity was tested through triangulation of sources, techniques, and time. The results of the study indicate that digital transformation through the use of social media, improved product packaging, and the use of production technology can expand marketing reach and increase the economic value of local coffee. Supporting factors include PKBM training, internet access, and community motivation, while inhibiting factors include limited digital literacy and technological facilities. The implications of this study indicate that PKBM plays a strategic role as an agent of community empowerment in encouraging sustainable digital transformation to improve the economic welfare of rural communities.